Nandrolone effects on men’s semen parameters in Erbil city - Sharef, Abdalmuhaimn Y.; Tawfeeq, Govand Sh.; Rasoul, Asos M. (Zanco Journal of Medical Sciences (ZJMS), 2017)
Background and objective: Anabolic androgenic steroids are synthetic compounds based on the structure of testosterone, and are used to treat various conditions such as reproductive system dysfunction. High doses of anabolic androgenic steroids and exercise influence the hypothalamic pituitary gonadal axis, which can, in turn, affect testicular apoptosis. This study aimed to investigate the influence of anabolic androgenic steroids on semen parameters in bodybuilders (heavy exercise) in Erbil city. Methods: Semen specimens and serum were collected from 150 which divided into three groups; each consists of 50 men. The control group (A) didn't practice exercise so didn't receive nandrolone. The exercise group (B) who practice daily without taking nandrolone. The exercise and treated group (C) who practice exercise and had been using nandrolone (200 mg- wk-1, intramuscularly) for at least three months. Smear prepared by methyline blue stain and assessment of semen volume, sperm morphology, sperm concentration ,motility were carried out .Serum levels of follicle-stimulating hormone, luteinizing hormone, and testosterone were also carried out. Results: There was no difference in the semen volume within three groups. Sperm concentration and the percentage of sperm motility in the group C was significantly lower (P <0.001) than that in the other groups. A significantly increased percentage of sperm with the tapered head was found in the group C. Our results also demonstrated a significant decrease in testosterone and follicle-stimulating hormone in the group C compared to group A and B. Conclusion: Users of anabolic-androgenic steroids have sperm with abnormal shape, especially tapered head, and low concentration of sperm with sluggish motility attributing to infertility.